Ubiquitin diGLY proteomics as an approach to identify and quantify the ubiquitin-modified proteome - Fulzele, Amit (Methods Mol Biol, 2018)
Protein ubiquitylation is one of the most prevalent post-translational modifications (PTM) within cells. Ubiquitin modification of target lysine residues typically marks substrates for proteasome-dependent degradation. However, ubiquitylation can also alter protein function through modulation of protein complexes, localization or activity, without impacting protein turnover. Taken together, ubiquitylation imparts critical regulatory control over nearly every cellular, physiological, and pathophysiological process. Affinity purification techniques coupled with quantitative mass spectrometry have been robust tools to identify PTMs on endogenous proteins. A peptide antibody-based affinity approach has been successfully utilized to enrich for and identify endogenously ubiquitylated proteins. These antibodies recognize the Lys-ϵ-Gly-Gly (diGLY) remnant that is generated following trypsin digestion of ubiquitylated proteins, and these peptides can then be identified by standard mass spectrometry approaches. This technique has led to the identification of >50,000 ubiquitylation sites in human cells and quantitative information about how many of these sites are altered upon exposure to diverse proteotoxic stressors. In addition, the diGLY proteomics approach has led to the identification of specific ubiquitin ligase targets. Here we provide a detailed method to interrogate the ubiquitin-modified proteome from any eukaryotic organism or tissue.